Strategic Management of Small and Medium Enterprises in The Digital Economy: The Experience of Uzbekistan and Global Practice - Akhmedov Donior Bakhromovich (Research Parks Publishers, 2026)
This scientific article analyzes the challenges and contemporary solutions related to the strategic management of small and medium enterprises (SMEs) in the context of the digital economy. The article examines the development indicators of SMEs in the Republic of Uzbekistan, the processes of digital transformation, and the effectiveness of strategic management models. Based on research findings, it has been proven that the adoption of digital technologies increases SME efficiency by 34-47% and significantly improves market competitiveness. The article presents theoretical foundations, empirical data, and practical recommendations.